A COMPARISON ON THE EFFECTIVENESS OF YOGA AND AROMATHERAPY MASSAGE USING LAVENDER TO DECREASE BLOOD PRESSURE IN ELDERLY - Hadi Kusuma Atmaja; Dina Fithriana (Jurnal Kesehatan Prima, 2017)
Abstract: The more a person’s age will affect the physical change. It may cause a change of cardiovascular system. One of ailments caused by cardiovascular change is hypertension. It is a leading cause of death in the world. One of the hypertension management is Yoga that can cause vasodilation of blood vessels and blood flow thus it can lower blood pressure. The purpose in the study was to identify the effectiveness of Yoga gymnastics compared by Aromatherapy massage using Lavender to decrease blood pressure in Nursing Home of Tresna Werda Puspakarma Mataram. The research used pre-experimental design namely two group pretest-posttest designs with sampling technique was purposive sampling. The sample was 20 respondents in each group that in accordance with criteria which have been set. The instrument was observation guideline and data analysis employed t-test. The result of statistical test on 9 respondents in each treatment group indicated there was a significant change of respondents’ blood pressure who were given either Yoga exercises or Aromatherapy massage using Lavender with t-count was higher than t-table (2.26), whereas Aromatherapy massage (t-count = 7.30) was more effective than Yoga activity (t-count = 4.296) to decrease blood pressure in Elderly. It can be concluded that Aromatherapy massage using Lavender is more effective than Yoga activity in decreasing Elderly’s blood pressure in Nursing House of Tresna Werda Puspakarma Mataram. This research is expected to be applied as one of therapy to figure out the increasing of blood pressure especially in Elderly.